1996
DOI: 10.1002/etc.5620150924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to an organophosphorus pesticide on the behavior and use of cover by captive starlings

Abstract: Abstract-It has been suggested that reduced behavioral activity of birds exposed to anticholinesterase pesticides could bias measures of exposure in field studies if the worst-affected individuals were underrepresented in samples collected by shooting or netting. To assess the likely scale of such biases, European starlings (Sturnus vulgaris) were housed in large aviaries containing simulated bushes made from natural vegetation. Each bird was given a near-lethal dose of the organophosphorus pesticide chlorfenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…The present results differ from those of other studies which report increased bird locomotor activity after fungicide ingestion (Fryday et al, 1996;Parker and Goldstein, 2000), probably because the doses involved were very different. The latter authors used near-lethal doses of a wettable powder solution (Parker and Goldstein, 2000) or a liquid form diluted with corn oil (Fryday et al, 1996).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The present results differ from those of other studies which report increased bird locomotor activity after fungicide ingestion (Fryday et al, 1996;Parker and Goldstein, 2000), probably because the doses involved were very different. The latter authors used near-lethal doses of a wettable powder solution (Parker and Goldstein, 2000) or a liquid form diluted with corn oil (Fryday et al, 1996).…”
Section: Discussioncontrasting
confidence: 99%
“…Maneb is of moderately low toxicity to birds (Gosselin et al, 1984) although acute doses can induce severe symptoms such as hypotonia, slow breathing and bradycardia, functional abnormalities of the thyroid and liver, hyperactivity with lack of coordination, loss of muscular tone, nausea, vomiting, loss of appetite, weight loss, delayed reflexes, respiratory paralysis and death (Smith, 1992;Fryday et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The ecological importance of this is that the damage to non-target species in the environment and such attribute of the organism could be effectively used as toxicity biosensor of chemical stress. Other studies on different toxicants especially petroleum related hydrocarbon compounds indicated damage to epithelial cells of the gill chamber (Omoregie 1995), destruction of liver (Omoregie 1995), possible nervous breakdown, failing organs and retarded physiological processes in fish body functions (Omoregie 1995Meyer et al 1992and Fryday et al 1996. Chindah et al (2001) noted that aquatic organisms (shell and fin fishes) which is indirect continuous contact with the medium in addition to breathing and feeding will be vulnerable to respiratory tract damage and other organs of the body.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of AChE by such compounds causes a build-up of ACh in the synapse, leading to a disruption of normal functioning of the nervous system . Acute toxicity can result in death by respiratory or cardiovascular arrest, or both, and because cholinergic innervation of the body is nearly ubiquitous, sublethal exposures can lead to a range of biochemical, physiological and behavioural effects (Fryday et al 1996;Grue et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It is an accepted diagnostic convention that whole-brain ChE inhibition >50% is indicative of anti-ChE exposure as the cause of death in avian mortality events (Ludke et al 1975;Hill and Fleming 1982). Further, various physiological and behavioural changes have been associated with brain ChE activity when inhibited to 40-60% of unexposed levels (Hart 1993;Vyas et al 1995;Fryday et al 1996;Tamura et al 2001). Though little is known about the function of ChEs in the plasma, their inhibition can be used to assess anti-ChE exposure and aid in diagnosing behavioural or physiological effects (Thompson 1991).…”
Section: Introductionmentioning
confidence: 99%